Laser‐Induced Swelling of Borosilicate Glasses—An Analysis of Associated Microstructural Development. (17th March 2014) - Cheng, Shangcong; Logunov, Stephan; Streltsov, Alexander
<x xml:space="preserve">Abstract</x> Borosilicate glass swelling by laser irradiation is an unusual phenomenon. The height of raised hemisphere on the swelled glass surface can be approximately 10–15% of the 1–3 mm glass thickness. To understand the mechanism of glass swelling, the micro‐structural information of swelled glasses is essential. Several transmission electron microscopy (TEM) techniques, including bright field image (BFI), selected area electron diffraction (SAED), energy dispersive spectroscopy (EDS), and electron energy loss spectroscopy (EELS) analysis, were used to find out the possible microstructure changes of the swelled glasses. Transition metal nanoparticles or alkali metal segregations as well as gas bubbles in the swelled glasses were identified. These observations suggest that reduction of glass components may provide oxygen to form bubbles, which can increase in size due to thermal effects of the laser radiation and lead to the glass swelling.